Designing a Credit Facility for Women Entrepreneurs : Lessons from the Ethiopia Women Entrepreneurship Development Project - Alibhai, Aly Salman; Achew, Mengistu Bessir; Strobbe, Francesco; Coleman, Rachel Dawn (World Bank, Washington, DC, 2020)
In October 2012, the Government of Ethiopia launched the Women Entrepreneurship Development Project (WEDP), with the aim of increasing the earnings and employment of growth-oriented micro and small enterprises (MSEs) owned or partly-owned by women entrepreneurs in Ethiopia. In doing so, it created the first ever women-entrepreneur focused line of credit in Africa, and one of few such operations in the world. In addition to the USD 45.9 million in financing, WEDP also offered a variety of innovative training opportunities, designed to not only enhance the business skills of its clients, but their entrepreneurial mindset and practices as well.